Comportamentos sexuais de risco nos adolescentes : resultados do estudo HBSC 2018 - Ramiro, Lúcia (2019)
Not using condom and engaging in sexual intercourse under the influence of alcohol or drugs have been long identified as sexual risk behaviours, particularly for adolescents. Participants were 5695 adolescents, of which 46.1% were boys, with a mean age of 15 years old. Most of the adolescents are Portuguese, attend the 8th year, the 10th year or the 12th year. The measures included asking the adolescent whether he or she had already had a romantic relationship, sexual intercourse, age of first sexual intercourse, condom use in last sexual intercourse, sexual intercourse under the influence of alcohol or drug, HIV testing and HPV vaccine. Gender and school years were also analysed. The majority reported having never had sexual intercourse (77.0%). Among those who answered affirmatively, they referred having had their first sexual intercourse at 15 years old. A significant minority reported not having used condom at last sexual intercourse (34.1%) and having had sexual intercourse under the influence of alcohol or drugs (14.5%). It was found that boys are those who use condoms more often, have sexual intercourse associated with the consumption of alcohol or drugs and do not have the HPV vaccine. And the younger boys of the 8th year are those that most often have sexual intercourse associated with the consumption of alcohol or drugs. These results may represent significant changes in educational and health policies, directing these towards the development of personal and social skills, and the activation of all the support structures where adolescents are involved. AIDS related campaigns and sexual education in school context within a health education context must be revitalized.